Dental caries experience and treatment needs of an adult female population in Nigeria (2017)
Experience and awareness of adult females concerning dental caries is important in its prevention particularly in children because of their natural role as care givers. To determine the prevalence of dental caries and treatment needs in an adult female Nigerian population. In this cross-sectional study, adult females attending outreach programmes were examined for dental caries using the Decayed Missing and Filled Teeth caries index (DMFT). Socio-demographic variables were also recorded and statistical analysis done with SPSS software. A total of 430 females aged 16 to 59 years participated in the outreach programme out of which 109 (25.3%) had a DMFT score > 0. Mean DMFT was 0.7 ± 1.6. Fifty-five (12.8%) participants had decayed teeth, 78 (18.1 %) had missing teeth and 10(2.3%) had filled teeth. The treatment need was 34.3%, restorative index was 13.3% and significant caries index was 2.0. There were significant differences in caries experience based on age, marital status and educational qualifications of participants p < 0.05. The prevalence of dental caries among the study group was low but the treatment need was high. Younger females, singles and those with lower educational qualifications had a higher dental caries experience